Vatican II and the ecumenical way - Tavard, George H. (George Henry), 1922-2007 (Marquette studies in theology, 2007)
"This book was born from the author's ecumenical experience and theological reflection. Formed in theology in France, where Henri de Lubac was one of his professors, the author also knew Jean Danielou and Yves Congar well. He is thus well acquainted with what came to be called the 'new theology, ' while his doctoral thesis on St. Bonaventure anchored his thought in the great century of scholastic theology." "In the perusal of this new book the reader will be guided through the problems, difficulties, intricacies, and also the hopes, possibilities, and discoveries of the ecumenical way. He or she should be led to see why John Paul II, who also had experienced Vatican II, declared the ecumenical commitment of the Catholic Church to be "irrevocable.""--Jacket.